Soil Improvement using Cement Deep Mixing (Case study: Dredging of the Channel and Port Basin of Benoa) - Mahardhika, Bogie Prastowo; Suharyanto; Nugroho, Hari (Universitas Islam 45, 2025)
The problem we often encounter in the field of geotechnics, especially in Indonesia, is soft soil. The characteristic of soft soil is low bearing capacity. During the dredging process of the harbor basin, the soft soil in the harbor may experience movement. Therefore, a system is needed to retain the soil on the land side of the port in the form of sheet piles. However, the safety factor does not meet the requirements. Therefore, soil improvement is necessary to maintain soil stability by increasing the soil's shear strength, one of the methods that can be used is Cement Deep Mixing (CDM). This research aims to determine the required ratio of the area to be repaired. The analysis was conducted using the finite element method (FEM) with PLAXIS 2D. The research results show a CDM Improvement Ratio of 50%, a width of 20 m, and a depth of 35 m. The reinforcement includes Steel Pipe Sheet Pile (SPSP) with a diameter of 711.2 mm, a thickness of 16 mm, and a depth of 37 m, as well as Spun Pile anchors with a diameter of 800 mm, a thickness of 120 mm, and a depth of 20 m, with a distance of 2.2 m between each anchor and a distance of 15.76 m from the sheet pile. The modeling data used is the CDM soil improvement data from the Benoa Harbor Dredging Project, Indonesia.